Mutiny on the Bounty - Nordhoff, Charles, 1887-1947.; Hall, James Norman, 1887-1951 (Boston : Little, Brown, and Co., 1932)
A British crew mutinies against the cruel commander of the Bounty in 1787.
Lieutenant Bligh -- Sea law -- At sea -- Tyranny -- Tahiti -- Indian household -- Christian and Bligh -- Homeward bound -- Mutiny -- Fletcher Christian -- Last of the bounty -- Tehani -- Moon of Pipiri -- Pandora -- Doctor Hamilton -- Roundhouse -- Search for the Bounty -- Last of the Pandora -- ten weary months -- Sir Joseph Banks -- H.M.S. Duke -- Case for the crown -- Defense -- Condemned -- Tinkler -- Withycombe -- Epilogue.
Keywords: Bligh, William, -- 1754-1817 -- Fiction; Bounty (Ship) -- Fiction; Bounty Mutiny, 1789 -- Fiction; Admirals -- Fiction; Biographical fiction; Sea stories; Great Britain -- History, Naval -- 18th century -- Fiction; Sea stories; Biographical fiction; Historical fiction